Modulation in structural and electronic properties of 2D Ga2O3 by chemical passivation. Issue 36 (21st August 2020) - Dong, Linpeng; Zhou, Shun; Gong, Lei; Wang, Wei; Zhang, Lichun; Yang, Chuanlu; Yu, Jianhui; Liu, Weiguo
Abstract : The dangling bonds on the surfaces of 2D Ga2 O3  can be effectively passivated by hydrofluorination, making 2D Ga2 O3  with ultra-high carrier mobility and bipolar transport property.  Abstract : Wide-bandgap semiconductor β-Ga2 O3 with fascinating optical–electrical characteristics and low-cost processed fabrication has gain wide attention. Recently, exfoliated quasi two-dimensional (2D) Ga2 O3 with excellent properties has received both experimental and theoretical attention. However, the stability of 2D Ga2 O3 is reduced by the abrupt absence of interlayer interactions, and the possibility of p-type conduction for 2D Ga2 O3 is not clear up to now. Herein, we investigated atom-passivated 2D Ga2 O3 using first-principles, the atomic configurations, formation energies, and electronic structures were calculated and examined. The results indicate that the dangling bonds on the surfaces are effectively passivated and the stability is elevated for hydrofluorinated Ga2 O3, which possesses a wide direct bandgap (5.547 eV) and ultra-high carrier mobility (∼10 3 cm 2 V −1 s −1 ). The acoustic phonon-limited mobility μ reveals the potential of bipolar transport property ( μ e b / μ h b is ∼2.45) for 2D Ga2 O3 along the b direction. Furthermore, layer-dependent properties of hydrofluorinated 2D Ga2 O3 were discussed. Our study offers an effective approach to modify the stability and electronic properties of 2D Ga2 O3, and supplies a new strategy to realize p-type conducting Ga2 O3 .